Aplikasi Pembelajaran Pengenalan Benda Di Lingkungan Sekitar Rumah Untuk Anak Berkebutuhan Khusus (Autis) Berbasis Kinect - Indahsari, Hanif Nur, Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Children with special needs like autism are children who experience communication and social interaction disorders and experience disturbances in censoring, playing pattern, and emotional. Therefore, in daily life, children with special needs are necessary to train their ability in doing social interaction, especially in identifying objects around their home with a method of learning more interesting is the educational game. The objective of this 2-dimensional educational game for children to recognize objects in the environment around home which are the things belong to home yard such as flowers, vegetables, etc. Researchers took the problems correspond with their learning curriculum based on the book Siswa Autis Tema 8 "Lingkungan Sekitar Rumah". The existing problems are used as a guidance in constructing and making Educational Game relates to the introduction and the ability that are improved for children with autism by using Kinect Xbox 360 technology. This educational game also by using Unity software, CorelDraw X6 and Dragonebones. The research was conducted by interviewing the teachers of the Rumah Pintar ABK Salatiga. The testing system was implemented in a way demonstrating educational game especially for the 2nd grade of Elementary School at Rumah Pintar ABK Salatiga and accompanied by teachers. The results of the assessment of teachers in filling out the questionnaire said that they agreed that the educational games can be interesting and interactive learning with Kinect sensor that is used to training the motor skills of children. The use of Kinect in Educational Game for developing recognition and knowledge about objects around home so that children with autism can recognise as well as increase their knowledge which variety of learning by teachers or adults' help in playing it. Keywords : children with autism, educational game, Kinect Xbox 360, Unity.